Eurasia twenty years after - Sengupta, Anita; Chatterjee, Suchandana; Bhattacharya, Susmita (Maulana Abul Kalam Azad Institute of Asian Studies, 2012)
Papers presented at the International Seminar: Eurasia Twenty Years After : 1991 in Retrospect, held at Maulana Abul Kalam Azad Institute of Asian Studies in February 2011
Includes bibliographical references and index
Keywords: Eurasia -- Congresses -- History; Eurasia -- Congresses -- Foreign relations; Konferenzschrift